2018
DOI: 10.1111/jopr.12743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Liners on Fracture Resistance of Premolars Restored with Conventional and Short Fiber‐Reinforced Composite Resins

Abstract: The four liners can be used without interfering with the higher efficacy of SFRC, compared to conventional composite resins, to improve the fracture strength of premolar MOD cavities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Yet, it was demonstrated that a flowable liner probably bonds and polymerizes simultaneously, leading to viscoelastic flow that reduces the negative effect of polymerization stress on the bonding. This property is advantageous in terms of marginal adaptation [ 56 ].…”
Section: Development Of Discussionmentioning
confidence: 99%
“…Yet, it was demonstrated that a flowable liner probably bonds and polymerizes simultaneously, leading to viscoelastic flow that reduces the negative effect of polymerization stress on the bonding. This property is advantageous in terms of marginal adaptation [ 56 ].…”
Section: Development Of Discussionmentioning
confidence: 99%
“…I.d) Fracture resistance test The specimens were subjected to thermoycling (1200 cycles) between 5°C and 55°C, with a dwell time of 30 seconds. Afterwards, all the specimens were subjected to load cycling of 240,000 cycles that simulates one year of clinical service in a custom made chewing simulator device prior to fracture resistance testing procedure (15). Axial compression was applied in a universal testing machine (5ST, Tinius Olsen, England) (Figure 1) using a 4-mm diameter metal ball with a crosshead speed of 0.5 mm/minute until fracture occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Before to embedding the teeth in a cylinder of self-curing acrylic resin up to 1 mm below the cementoenamel junction (CEJ), their roots were covered with a 0.2-0.3-mm layer of melted wax. This layer was replaced with a polyether impression material to mimic the periodontal ligament (17). The long axis of the tooth was perpendicular to the base of the cylinder.…”
Section: Methodsmentioning
confidence: 99%